2014
DOI: 10.7750/biodiscovery.2014.13.1
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage and the circadian clock

Abstract: The role of the circadian clock has already been demonstrated for virtually all physiological processes, but it was only recently shown that cells were more sensi ve to DNA damage at specific mes of the day; that the peak of synthesis of mRNA and proteins of genes coding for products involved directly or indirectly in DNA repair was differen ally med in different ssues; and that the growth of some types of cancer followed a circadian pa ern. The paper reviews the specifici es of the clockwork mechanism in livi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 268 publications
0
4
0
Order By: Relevance
“…The DDR preserves genetic stability by detecting DNA lesions, activating cell cycle checkpoints and promoting DNA damage repair [18][19][20][21]. The common denominator integrating these forms of genotoxic stresses and eliciting the signalling cascade is increased production of ROS as harbinger to DNA damage [22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…The DDR preserves genetic stability by detecting DNA lesions, activating cell cycle checkpoints and promoting DNA damage repair [18][19][20][21]. The common denominator integrating these forms of genotoxic stresses and eliciting the signalling cascade is increased production of ROS as harbinger to DNA damage [22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Shi et al pointed out the enhanced DMN‐ACN functional connectivity was involved in sustained hypervigilance and hyperarousal, and it could reflect the function of self‐reflection, emotional regulation and cognitive control. Also, the cortisol secretion levels of MCPs were significantly higher than ECPs at 10 h after awakening, 45 which may be manifested by heightened arousal, including hypersensivity to various stimuli and/or hypervigilance 46 . Moreover, MCPs showed a higher total amount of cortisol and there was a significantly shortened phase of cortisol increase within the first hour after awakening, 47 which suggested that MCPs may increase cortisol secretion levels after a longer period of awakening and enhance arousal.…”
Section: Discussionmentioning
confidence: 92%
“…Also, the cortisol secretion levels of MCPs were significantly higher than ECPs at 10 h after awakening, 45 which may be manifested by heightened arousal, including hypersensivity to various stimuli and/or hypervigilance. 46 Moreover, MCPs showed a higher total amount of cortisol and there was a significantly shortened phase of cortisol increase within the first hour after awakening, 47 which suggested that MCPs may increase cortisol secretion levels after a longer period of awakening and enhance arousal. Although stronger anti‐correlation of rsFC between DMN and ACN may be accompanied by better performance, it may also represent mere negative emotion and arousal.…”
Section: Discussionmentioning
confidence: 98%
“…14 Higher efficacy and better tolerability of timed platinum-based systemic chemotherapy have been demonstrated in several experimental models. [15][16][17][18][19] Hyperthermic intraperitoneal chemoperfusion (HIPEC) is a type of locoregional chemotherapy which is used in combination with cytoreductive surgery for certain types of cancer affecting the peritoneum. 20 Local hyperthermia along with high doses of the drugs enhances the penetration of the drugs into residual tumor nodes left after surgery.…”
Section: Introductionmentioning
confidence: 99%